Efficiency of antimicrobial photodynamic therapy with photodithazine® on mssa and mrsa strains - Nunes Souza, Beatriz Müller (2021)
Staphylococccus aureus is a ubiquitous and opportunistic bacteria associated with high mortality rates. Antimicrobial photodynamic therapy (aPDT) is based on the application of a light source and a photosensitizer that can interact with molecular oxygen, forming Reactive Oxygen Species (ROS) that result in bacterial inactivation. This study aimed to analyze, in vitro, the action of aPDT with Photodithazine® (PDZ) in methicillin-sensitive Staphylococcus aureus (MSSA) and methicillin-resistant Staphylococcus aureus (MRSA) strains. The strains were incubated with PDZ at 25, 50, 75, and 100 mg/L for 15 min and irradiated with fluences of 25, 50, and 100 J/cm2 . The internalization of PDZ was evaluated by confocal microscopy, the bacterial growth by counting the number of colony-forming units, as well as the bacterial metabolic activity post-aPDT and the production of ROS. In both strains, the photosensitizer was internalized; the production of ROS increased when the aPDT was applied; there was a bacterial reduction compared to the control at all the evaluated fluences and concentrations; and, in most parameters, it was obtained complete inactivation with significant difference (p < 0.05). The implementation of aPDT with PDZ in clinical strains of S. aureus has resulted in its complete inactivation, including the MRSA strains.